Simple and effective method to protect from toxic fumes of methyl methacrylate (bone cement) in operation theatre - E. G., Mohan Kumar; G. M., Yathisha Kumar; Noorudheen, Mohammed; Kumar, Ajay (International Journal of Research in Orthopaedics, 2019)
Methyl methacrylate is a monomer of acrylic resin widely used in a variety of medical, dental, and industrial applications. Its extensive use in surgery, particularly for arthroplasties, has often raised concerns regarding potential human toxicity for orthopaedic surgeons, surgical nurses, and other operating-room staff who are occupationally exposed to the compound.